[11C]carfentanil PET imaging for studying the peripheral opioid system in vivo: effect of photoperiod on mu-opioid receptor availability in brown adipose tissue - Sun Lihua; Aarnio Richard; Herre Erika Atencio; Kärnä Salli; Palani Senthil; Virtanen Helena; Liljenbäck Heidi; Virta Jenni; Honkaniemi Aake; Oikonen Vesa; Han Chunlei; Laurila Sanna; et al. (Springer, 2022)
Purpose Photoperiod determines the metabolic activity of brown adipose tissue (BAT) and affects the food intake and body mass of mammals. Sympathetic innervation of the BAT controls thermogenesis and facilitates physiological adaption to seasonal changes, but the exact mechanism remains elusive. Previous studies have shown that central opioid signaling regulates BAT thermogenesis, and that the expression of the brain mu-opioid receptor (MOR) varies seasonally. Therefore, it is important to know whether MOR expression in BAT shows seasonal variation.
Methods We determined the effect of photoperiod on BAT MOR availability using [C-11] carfentanil positron emission tomography (PET). Adult rats (n = 9) were repeatedly imaged under various photoperiods in order to simulate seasonal changes.
Results Long photoperiod was associated with low MOR expression in BAT (beta = -0.04, 95% confidence interval: - 0.07, - 0.01), but not in muscles. We confirmed the expression of MOR in BAT and muscle using immunofluorescence staining.
Conclusion Photoperiod affects MOR availability in BAT. Sympathetic innervation of BAT may influence thermogenesis via the peripheral MOR system. The present study supports the utility of [C-11]carfentanil PET to study the peripheral MOR system.